STRATEGI KOMUNIKASI PEMASARAN BATAM ELEKTRONIK DALAM MEMPERTAHANKAN LOYALITAS PELANGGAN DI KOTA PEKANBARU - T.Adelia Miranda K; Muhammad Firdaus (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
In the current era of Globalization business behavior especially in the field of marketing has increased over time. Currently, many companies are competing to win the competition and mastered by means of utilizing and, applying the right marketing can not be denied mastery of the market is one way the company to sustain its life. One of which is how to create conditions by keeping customers from turning against other companies or products.The purpose of the research is to determine the marketing communication strategy used by a company to maintain customer loyalty And to know Factors inhibiting Marketing Communications strategy.This research method is qualitative research method by presenting descriptive data analysis and using strategic communication theory. The research technique is based on purposive technique consisting of head of shop, 4 marketing and 10 consumen of Batam Electronics. Techniques Data collection includes observation, interviews, and documentation. Data analysis techniques using interactive data models Miles and Huberman. While the examination techniques of validity data include extension of participation, triangulation and reference adequacy.The result of the research shows the first communication strategy of Batam Electronic Marketing in maintaining Customer Loyalty through advertising, sales promotion, personal selling, direct selling. Second, the factors that inhibit the implementation of marketing communications Batam Pekanbaru Electronic in maintaining Customer Loyalty is the lack of advertising through Television and Radio, lack of Manpower Resources, Lack of Sales off the field and lack of good relationship between superiors with subordinatesKeyword: Batam Elektronik,Communication Strategy,Costumer